Applied network security monitoring collection, detection and analysis - Sanders, Chris (Syngress is an imprint of Elsevier, 2014)
This book is a guide to becoming an Network Security Monitoring (NSM) analyst. It follows the three stages of the NSM cycle: collection, detection, and analysis, and features real-world examples